PENGARUH MODEL INKUIRI TERBIMBING TERHADAP KETERAMPILAN BERPIKIR KREATIF MAHASISWA PADA PRAKTIKUM ANALISA PROTEIN - Sulistiana, Dewi Anugrah; Supriyanti, F.M. Titin; Solihin, Hayat (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2016)
This study aims to determine the effect of guided inquiry model to the creative thinking skill (KBKr) of students on practicum protein analysis. Creative thinking skills developed include flexibility, fluency and elaboration. The research method used was quasi experiment with non control equivalent pretest-postes design group. Research subjects involve Chemistry study program students in one State University in Bandung consisting of 18 students in the experimental class and 19 students in the control class. The instrument used is a 5 item description that measures KBKr and student worksheets. The data analysis was performed by determining the normalized t-gain standardized (N-gain) value with the help of SPSS 20 program for windows and Microsoft excel 2010. The result of N-gain average value analysis shows that there is a higher KBkr increase in students who follow lab With guided inquiry model compared to control class students with the distribution of KBKr being in the high and moderate category for the experimental group, and the moderate and low category in the control class. The statistical test of mean difference of KBKr with Mann-Whitney technique showed significant difference of student KBKr in the experimental class and control class on flexibility and fluid indicator. This suggests that the application of guided inquiry models can be used as an alternative model for increasing KBKr in biochemical learning.